Black religion and the imagination of matter in the Atlantic World - Noel, James A., 1948- (Black religion, womanist thought, social justice., 2009)
This book situates the study of Black Religion within the modern temporal and historical structures whose geographical contours are the Atlantic World. It describes how black people and Black Religion made a phenomenological appearance in modernity simultaneously and were signified in the identity formation of whites and their religion. James A. Noel accounts for these new identity formations, religious-social practices, and their accompanying epistemological orientations by describing the non-reciprocal contacts and exchanges from which ensued new modes of materiality and imagining matter. Black Religion is shown to represent an alternative epistemological mode of imagining matter and a critique of both white Christianity and the Enlightenment.